Penguatan Budaya Digital Berkarakter melalui Metode Permainan pada Siswa Sekolah Dasar di Rawamangun, Jakarta Timur - Kharis, Selly Anastassia Amellia; Permatasari, Sri Maulidia; Humaira, Sajida; Arisanty, Melisa; Sukatmi, Sri; Muzammil, Moh; Karim, Muhammad Firman; Pangaribuan, Nurmala (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Character-based digital culture is a fundamental competency that every child should posses, particularly in responding to the rapid development of digital technology. It serves as an important foundation for shaping national identitiy and guiding the attitudes of younger generations in addressing various issues amid globalization and digital transformation. One effort to strengthen this culture is through game-based activities designed in an educational and contextual manner. These activities integrate national character values into the use of the digital world. The objective of this activity is to enhance character-based digital culture among elementary school students through a game-based approach. The participants were elementary school students in Rawamangun, East Jakarta. The method employed is an educational and game-based training approach. The evaluation results indicate an improvement in participants’ understanding of character-based digital culture. Therefore, games-based activities can serve as an effective alternative learning model for fostering national character values in digital interactions.